Reconstructing the Role of Logic and Reasoning in Scientific Inquiry: An Epistemological Perspective - Boby Yasman Purnama; Ahmad Syukri; Badarussyamsi; Wardatul Jannah (International Journal of Education, Language, and Social Science, 2025)
Logic and reasoning constitute the fundamental intellectual instruments through which scientific knowledge is generated, evaluated, and justified. Despite their central role in the philosophy of science, contemporary scientific discourse is increasingly characterized by complex patterns of inquiry shaped by digital technologies, interdisciplinary collaboration, and evidence-based decision-making. These developments necessitate a renewed examination of the epistemological functions of logic and reasoning within scientific inquiry. This study aims to reconstruct the conceptual relationship between logic, reasoning, and scientific knowledge by examining their philosophical foundations and their relevance to contemporary scientific practice. Employing a qualitative library research approach, this study critically analyzes classical and contemporary literature in philosophy, logic, and the philosophy of science. The findings demonstrate that logic provides the normative framework for valid thinking, while reasoning functions as the cognitive process through which evidence, arguments, and observations are systematically interpreted to construct scientific knowledge. Furthermore, the analysis reveals that the interaction between logic and reasoning underpins hypothesis formulation, theory development, scientific verification, and critical evaluation, making both indispensable components of scientific inquiry. This study contributes to the philosophy of science by offering an integrated epistemological interpretation that positions logic and reasoning as complementary foundations for the development of reliable, rational, and evidence-based scientific knowledge in the twenty-first century.